The Gontor Way: Bringing Islamic Education to Sulawesi - Wekke, Ismail Suardi; Riswandi, Akmal (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
Beyond its renowned Ponorogo campus, the esteemed Islamic boarding school, Pondok Modern Darussalam Gontor (Gontor), has established a firm presence in Sulawesi. This abstract delves into Gontor's journey and impact across the diverse island, exploring its two established branches. Pondok Modern Darussalam Gontor 7